Leveraging mobile applications in humanitarian crisis to improve health: a case of Syrian women and children refugees in Turkey - Aral Surmeli; Nirmala P Narla; Angela J Shields; Rifat Atun (Inishmore Laser Scientific Publishing Ltd, 2020)
The open-door policy of Turkey has made it an attractive destination for millions of Syrians to escape the war. In Turkey, refugees can utilize health services free of charge, as individuals under temporary protection. However, the low uptake of preventive services including prenatal visits and childhood immunizations is a critical threat to the health of Syrian refugees and Turkish citizens. We designed an open-sourced mobile health (mHealth) platform, (HERA App), for Syrian women and children refugees in Turkey, to increase uptake of available preventive health services. HERA App is uniquely designed to reduce demand-side barriers that refugees encounter in relation to healthcare access and improve outcomes related to vaccine-preventable diseases and maternal health. HERA App provides solutions for healthcare navigation, health education, and behavioral nudges, such as automated reminders to increase timely childhood immunizations and pregnancy related doctor visits. HERA App is the first mHealth solution that has been designed for Syrian refugees in Turkey and is currently still in the data collection phase. We discuss its design and implementation and analyze the enablers and barriers of adoption systems, health systems access, and cultural norms for implementing a demand-side mHealth intervention in this context.